SOSIALISASI TEKNOLOGI ADAPTIF KELAUTAN DAN PERIKANAN DI KOTA TEGAL - Catur Pramono Adi (Fakultas Pertanian_Universitas Tidar, 2023)
In Indonesia the marine and fisheries sector has a strategic position both for foreign exchange contributions and for improving people's welfare. Therefore increasing the competence of the marine and fisheries community is an important thing that must be considered. To accommodate the increase in science and technology in the marine and fisheries sector, the Ministry of Maritime Affairs and Fisheries through the Marine and Fisheries Research and Development Agency in the 2013-2014 period published a KP Technology Recommendation book. The book contains 71 technologies that have been tested and their benefits recognized. Unfortunately, not many of these technologies have been introduced and adopted by society. Moving on from these conditions, in 2021 will carry out KP Adaptive Technology Technical Guidance activities which aim to socialize these technologies so that they can be adopted as needed at the location. This technical guidance activity was carried out in several locations, one of which was in Tegal City, Central Java. The main objective of this activity is to increase the competency of extension workers as a link between researchers and the community while also improving their work ethic. Technology material in this Bimtek consists of: 1). Tiger Shrimp Cultivation with the IMTA method; 2). Application of Pato Aero Probiotics in Catfish; 3). KGM as a breakwater; 4). Srikandi Tilapia Cultivation in Ponds; and 5). Aspects of Institutional Development and Business Control. Based on the results of an analysis of the pre and post test scores conducted by Bimtek participants in Tegal, most of the participants had an increased knowledge score in the range of 50-75% on 3 items and a score of 0-50% on 1 item. The lack of transfer of knowledge and technology can be caused by many factors, but the most important is the instructor's personal motivation in participating in this technical guidance activity. Recommendations that can be suggested for the implementation of this technical guidance activity in the following year are to focus more on technology material that will be transferred according to the needs at the location so that it can be effective and useful.